Observing Internal Solitary Waves in the Lombok Strait by Coastal Acoustic Tomography. Issue 17 (6th September 2019) - Syamsudin, Fadli; Taniguchi, Naokazu; Zhang, Chuanzheng; Hanifa, Aruni Dinan; Li, Guangming; Chen, Minmo; Mutsuda, Hidemi; Zhu, Ze‐Nan; Zhu, Xiao‐Hua; Nagai, Taira; Kaneko, Arata
Abstract: The subsurface structures of internal solitary waves were observed over two days from 27 to 29 February 2019, by two bottom‐moored coastal acoustic tomography systems over a path length of 18.286 km in the Lombok Strait, Indonesia. One‐way travel times along the transmission path between the acoustic stations were determined for the first three arrival peaks. The resulting three travel times were used to execute a four‐layer (0–50, 150–300, 300–450, and 400–603 m) temperature inversion, constructing an underdetermined problem. The inverted four‐layer temperatures show three positive peaks and two negative peaks during the observation period, implying the sequential passage of internal solitary waves with depressed and elevated interfaces. The generation of these temperature peaks is synchronized with the diurnal tides, and the peak heights decrease with depth. The inverted four‐layer temperatures are in excellent agreement with conductivity‐temperature‐depth data obtained near the acoustic stations. Plain Language Summary: Internal solitary waves (ISWs) are generated around continental shelf edges, the subsurface slopes of islands and seamounts, and sills in straits by an interaction between the permanent thermocline and strong barotropic tidal currents. ISWs induce sudden changes in the water temperature and severe hydrodynamic forces acting on structures such as oil platforms during their propagation to adjacent regions. Furthermore, water is strongly mixed by the breaking of large ISWs, enhancing the level of turbulence and influencing biological environments in the surrounding regions. Unlike the generation and propagation of ISWs detectable at the surface by synthetic aperture radar satellites, the subsurface structures of ISWs are beyond the spatial resolution limits of synthetic aperture radar satellites. Bottom‐moored coastal acoustic tomography is a new cost‐efficient and innovative technology for measuring the subsurface structures of ISWs propagating from a source region to surrounding regions. Key Points: Internal solitary waves generated in the Lombok Strait are measured by two bottom‐moored coastal acoustic tomography systems Four‐layer temperatures are reconstructed by a vertical‐slice inversion using one‐way travel times for the first three arrival peaks The inverted temperatures show five peaks with heights ranging from 3 to 6°C, implying the sequential passage of internal solitary waves